Two mechanisms of membrane digestion: enzymatic-transport ensemble exists - S. T. Metelsky; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To analyze initial stages of coupling between membrane hydrolysis of nutrients (sugar dimers) and membrane transport of formed monomers in rats and humans.Material and methods. Electrophysiological experiments carried out on resected segments of small intestine of rats weighted 160 to 550 g (85 animals). The group of patients included 19 person in the age of 17–80 years with abdominal ischemia syndrome, chronic gastritis, gastric ulcer, irritable bowel syndrome. Method of gastric of short circuit current (SCC) in original modification was used. Values of responses of current to addition of nutrients (monomers and sugar dimers) in the mucosa-washing solution, used accepted, as it is consented up to now, as a measure of Na+-dependent nutrient absorbtion rate.Results. SCC responses to glucose and maltose taken in 2:1concentration, under all tested conditions (85 pairs) appeared almost equal. The correlation coefficient was 0,992, linear regression equation was Аgl = 0,1 + 1,05 × Аml. Along with approach of maltose molecules to surface of enterocytes they without any delay, that could be necessary to fill certain hypothetical nearmembrane layer by molecules of released glucose, participate in development of the response of short circuit current. Hence, in rats Na+-dependent transport (absorbtion) of maltose and glucose is carried out by the same enzymatic-transport ensamble. For humans statement of the question on existence of enzymatic-transport ensemble due to initial disparity of serial responses to maltose (5 mM) and glucose (10 mM) makes no sense.Conclusions. In rats Na+-dependent transport of maltose and glucose is carried out by the same mechanism. In enterocyte brush border of animals there is enzymatic-transport ensemble splitting molecules of maltose in two molecules of glucose which are immediately transferred to transport system entrance (A.M. Ugolev). In humans such enzymatic-transport ensemble is absent. Free and maltose glucose, apparently, are transported through brush border of enterocytes by two various mechanisms.